A competitive design and material consideration for fabrication of polymer electrolyte membrane fuel cell bipolar plates - Hassan, Noor Ul; Tunaboylu, Bahadir Ir; Soydan, Ali Murat (MDPI AG diversity@mdpi.com, 2019)
The bipolar plate is one of the most significant components of a polymer electrolyte membrane (PEM) fuel cell, and contributes substantially to the cost structure and the weight of the stacks. A number of graphite polymer composites with different fabrication techniques have been reported in the literature. Graphite composites show excellent electromechanical properties and chemical stability in acidic environments. Compression and injection molding are the most common manufacturing methods being used for mass production. In this study, a competitive bipolar plate design and fabrication technique is adopted in order to develop a low-cost and light-weight expanded graphite (EG) polymer composite bipolar plate for an air-breathing PEM fuel cell. Cutting molds are designed to cut fuel flow channels on thin expanded graphite (EG) sheets (0.6 mm thickness). Three separate sheets, with the flow channel textures removed, are glued to each other by a commercial conductive epoxy to build a single bipolar plate. The final product has a density of 1.79 g/cm3. A bipolar plate with a 20 cm2 active area weighs only 11.38 g. The manufacturing cost is estimated to be 7.77 $/kWe, and a total manufacturing time of 2 minutes/plate is achieved with lab-scale fabrication. A flexural strength value of 29 MPa is obtained with the three-point bending method. A total resistance of 22.3 milliohms.cm2 is measured for the three-layer bipolar plate. We presume that the suggested design and fabrication process can be a competitive alternate for the small-scale, as well as mass production of bipolar plates. © 2020 Elsevier B.V., All rights reserved.
Keywords: Bipolar plate; Competitive design; Flexural strength; Graphite polymer composite; PEM fuel cell